Pemodelan Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Pia Jagung Dumati menggunakan Structural Equation Modeling-Partial Least Square - Abdussamad, Siti Nurmardia; Naue, Siti Nurmeylisya; Hasan, Nadia Kasmin (Research in the Mathematical and Natural Sciences, 2025)
The development of industrial competition requires producers to continue to evaluate and innovate the products they produce. This research aims to analyze consumer behavior by looking at the factors that influence the purchase of Pia Jagung Dumati products in Gorontalo Regency. The method used is Structural Equation Modeling (SEM)-Partial Least Square (PLS) to provide a clearer picture of the influence on consumer behavior. Questionnaires distributed to 100 respondents became the data used in this research. The sampling technique used is purposive sampling. This research uses the variables price, product quality, promotions, and working hours. The results of the analysis are that the price, product quality and promotion variables have a significant influence on consumer behavior, while the working hours variable has no significant influence. This research provides recommendations for manufacturers to focus on flavor innovation, packaging and more creative digital marketing strategies to attract the attention of consumers, especially among the productive age group